Impact of vaccination against the novel coronavirus infection (COVID-19) with Sputnik V on mortality during the delta variant surge - Ksenia Dmitrieva; Roman Maslennikov; Ekaterina Vasilieva; Salekh Aliev; Vyacheslav Bakhitov; Vadim Marcinkevich; Anna Levshina; Evgenii Kozlov; Vladimir Ivashkin; Elena Poluektova (Elsevier, 2023)
Objectives: The aim is to study impact of vaccination against the novel coronavirus disease (COVID-19) with Sputnik V on mortality during the period of predominance of the delta variant of SARS-CoV-2. Methods: This was a retrospective cohort study of individuals with state health insurance at the Moscow Ambulatory Center. The cohorts included 41,444 persons vaccinated with Sputnik V, 15,566 survivors of COVID-19, and 71,377 non-immune persons. The deaths of patients that occurred from June 1, 2021, to August 31, 2021, were analyzed. Results: Overall (0.39 % vs. 1.92 %; p < 0.001), COVID-19-related (0.06 % vs. 0.83 %; p < 0.001), and non-COVID mortality (0.33 % vs. 1.09 %; p < 0.001) was lower among vaccinated individuals than among non-immune individuals. The efficacy of vaccination against death from COVID-19 was 96 % [95 % CI 91-98 %] in the general population, 100 % among those aged 18-50 years, 97 % [95 % CI 76-100 %] among those aged 51-70 years, 98 % [95 % CI 90-100 %] among those aged 71-85 years, and 88 % [95 % CI 49-97 %] among those aged > 85 years. Conclusion: COVID-19 vaccination with Sputnik V is associated with a decrease in overall and COVID-19-related mortality and is not with increased non-COVID mortality.